Healthy Birth Practice #5: Avoid Giving Birth on Your Back and Follow Your Body’s Urge to Push - DiFranco, Joyce T. (J Perinat Educ, 2014)
Women in the United States are still giving birth in the supine position and are restricted in how long they can push and encouraged to push forcefully by their caregivers. Research does not support these activities. There is discussion about current research and suggestions on how to improve the quality of the birth experience. This article is an updated evidence-based review of the “Lamaze International Care Practices That Promote Normal Birth, Care Practice #5: Spontaneous Pushing in Upright or Gravity-Neutral Positions,” published in The Journal of Perinatal Education, 16(3), 2007.